2009
DOI: 10.1111/j.1365-277x.2009.01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Making an informed choice in the catering environment: what do consumers want to know?

Abstract: A significant proportion of consumers wish to see information on the ingredients and nutrition composition on menu items for sale in UK catering outlets. Such information is likely to raise an awareness and understanding of healthy food choices and assist the population in making informed choices about healthy eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
1
15
2
6
Order By: Relevance
“…British surveys have shown that people want to know what ingredients are present in the food they eat, and would take into consideration the ingredients information on menus [21,22]. However these studies did not reveal why consumers want this information and what ingredients consumers wanted to see on the menu, as was shown in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…British surveys have shown that people want to know what ingredients are present in the food they eat, and would take into consideration the ingredients information on menus [21,22]. However these studies did not reveal why consumers want this information and what ingredients consumers wanted to see on the menu, as was shown in our study.…”
Section: Discussioncontrasting
confidence: 66%
“…Discussion: A traffic light labelled menu with energy information appears to be popular and effective in signposting some customers towards healthier alternatives in a table service restaurant. The finding that the provision of this information on menus was particularly popular with women is supported by other studies (Mackison et al, 2009) and suggests a value of finding ways to increase the appeal to men. The finding that choosing a healthy main course option increased the likelihood of ordering dessert also mirrors previous research.…”
supporting
confidence: 61%
“…The benefits sought after by consumers, according to these scholars entail information on saturated fat levels, polyunsaturated fat components, fiber and sodium levels in food. Research finding by earlier scholars on healthy eating products on offer in hotels show that consumers seek for, apart from calorie content of food, the salt level and saturated fat contents in the foods they sample while eating out (Mackison et al, 2009). Customers, therefore, expected that products on offer in restaurants were in terms of what they perceived to be healthy food.…”
Section: Original Scientific Papermentioning
confidence: 99%